WHOLE LIFE ORDERS: ARTICLE 3 COMPLIANT AFTER ALL. (12th July 2017) - Bild, Jonathan
Abstract : The exercise of the Secretary of State's power to release from prison a murderer sentenced to a whole life order would be controversial and politically fraught. The Grand Chamber of the European Court of Human Rights' ("ECtHR") succinct summary of the offending leading to the whole life order imposed on the applicant in Hutchinson v United Kingdom (57592/08), Judgment of 17 January 2017, demonstrates quite why a Secretary of State would find exercising their compassionate release powers so politically unpalatable: "In October 1983, the applicant broke into a family home, where he stabbed to death a man, his wife and their adult son. He then repeatedly raped their 18-year-old daughter, having first dragged her past her father's body" (at [10]). Yet the power to release life sentence prisoners on compassionate grounds under s. 30 of the Crime (Sentences) Act 1997 has become the fig leaf covering a more fundamental disagreement between the domestic courts and the ECtHR: whether it is possible to commit offences of such gravity that, for the purposes of retribution and deterrence, a person must forfeit their right to liberty for the duration of their life.